THE THE IMAGE OF THE FAMILY IN THE THEMATIC PAINTINGS OF THE NATIONAL ARTIST OF UKRAINE ADOLPH LOZA - Лоза, Наталя Адольфівна; Носенко, Анна Іванівна (Art and Design, 2024)
Purpose of the article is to study the peculiarities of family images in the pictorial compositions of Adolf Ivanovich Loza (1931–2004) in the context of the time of their creation; to give an interpretation to the content of the images of the mother, the father, the child, and to analyze them from the standpoint of the embodiment of timeless archetypes. Methodology. Historical and cultural, artistic and stylistic, comparative, iconographic and iconological methods were employed in the research. The article analyzes the theme of family in the artist's paintings, which he addressed throughout his creative life. The main images are revealed: mother, father, childhood, family as a whole. The meaning of personal impressions and memories of childhood, the war and the post-war years is revealed in the image of the mother-berehynia. With this in mind, the author created a generalized image of the Mother-Woman-Earth, who gives birth, feeds, protects, takes care of the future generation, thereby continuing the family and preserving traditions. It is shown that the image of the Father is directly related to the image of the child (son). In the compositions, they act as a unity between generations, not only visually, but symbolically – one grows out of another, relies on experience and grows physically, mentally and spiritually. In the images of childhood, the artist reveals the theme of growth, growing up. It was found out that the images of the family in the artist’s works are the embodiment of timeless archetypes, which brings the imagery of the artist’s works to another global-mythological level. The images of the family in A.I. Loza's thematic compositions are studied in the context of the artist's time and personal experience; the semantic basis of the images of mother, father, and child is analyzed in relation to the problems of national mentality and common archetypes. The results of the research are necessary to create a complete picture of the art history of Ukraine and, in particular, the Odesa Art School.